2.8k views
3 votes
Evaluate the expression: –3^ – (–5^) – (15 – 33).

User Sukhhhh
by
5.5k points

1 Answer

3 votes

Answer:


\large\boxed{-3^2-(-5^2)-(15-33)=34}

Explanation:

Use PEMDAS:

P Parentheses first

E Exponents (ie Powers and Square Roots, etc.)

MD Multiplication and Division (left-to-right)

AS Addition and Subtraction (left-to-right)

------------------------------------------------------------------------------


-3^2-(-5^2)-(15-33)\\\\=-9-(-25)-(-18)\\\\=-9+25+18\\\\=34

User Ilya Suzdalnitski
by
4.9k points